Correlation between malondialdehyde level and FOXO3 and CASP3 mRNA expression changed in early-onset preeclampsia placenta - Ni Made Wiasty Sukanty; Febriana Catur Iswanti; Syarifah Dewi; Muhammad Faruqi; Alyssa Shafa Andiana; Ani Retno Prijanti (Acta Biochimica Indonesiana, 2021)
Background: Preeclampsia is one of the factors causing the high maternal mortality rate. The risk of morbidity and mortality is higher in Early Onset Preeclampsia (EOPE). Failure of spiral artery remodeling can cause oxidative stress that can inhibit placental development and increase trophoblast apoptosis. Objective: This study aims to analyze the oxidative stress and apoptosis of EOPE placentas. Methods: This study is an observational study with a cross-sectional design. A total of 31 EOPE placentas and 31 normal term placentas were used to measure the concentration of malondialdehyde (MDA) and the relative mRNA expression of FOXO3 and CASP3 using the spectrophotometric and RT-qPCR methods. Results: There was no difference in MDA concentration (p = 0.580) and FOXO3 (p = 0.467) and CASP3 (p = 0.243) mRNA expression in the normal and EOPE groups. There was a strong positive correlation between FOXO3 and CASP3 mRNA expression in the normal (p= 0.0001; r = 0.938) and EOPE groups (p = 0.0001; r = 0.855). There was no correlation between MDA concentration to FOXO3 (p = 0.124; r = 0.282) and CASP3 (p = 0.569; r = 0.106) mRNA expression in normal placenta. There was positive correlation between MDA concentration to FOXO3 (p = 0.016; r = 0.429) and CASP3 mRNA expression in EOPE placenta (p = 0.028; r = 0.395). Conclusion: These results indicate that cell integrity is still maintained through the autophagy process and the level of apoptosis in the EOPE placenta is regulated by ROS through FOXO3.